2020
DOI: 10.3390/biom10101459
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Amygdalin in Various Matrices Using Electrospray Ionization and Flowing Atmospheric-Pressure Afterglow Mass Spectrometry

Abstract: Amygdalin is a natural cyanogenic compound that plants produce in the fight against insects and herbivores. Excessive amounts of amygdalin by animals and humans can potentially lead to fatal intoxication. However, studies confirm that amygdalin has antitumor properties, including the ability to inhibit the proliferation of cancer cells and to induce their apoptosis. The analysis of amygdalin in various matrices is an important analytical problem today. The publication presents the methodology of direct determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(39 reference statements)
2
3
0
Order By: Relevance
“…Further, the amygdalin content was also analyzed. This was identified in the negative ion mode with m / z 456, molecular formula C 20 H 26 NO 11 , and its main product ion 323 as shown in Table S1 , in concordance with other authors that previously identified amygdalin [ 48 , 49 , 50 ]. Further, the negative-mode product ion chromatogram of amygdalin is shown in Figure S1 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Further, the amygdalin content was also analyzed. This was identified in the negative ion mode with m / z 456, molecular formula C 20 H 26 NO 11 , and its main product ion 323 as shown in Table S1 , in concordance with other authors that previously identified amygdalin [ 48 , 49 , 50 ]. Further, the negative-mode product ion chromatogram of amygdalin is shown in Figure S1 .…”
Section: Resultssupporting
confidence: 90%
“…According to Lee et al (2013) [ 48 ], the fragment ion 323 corresponds to amygdalin losing the disaccharide, as well as fragment ions of m / z 221 and 263 that were identified corresponding to the cross-ring bond cleavage of glucose A 2 . Additionally, the linkage of amygdalin with Cl − in concordance with Guć et al (2020) can be appreciated in the fragment ion m / z 492 [ 49 ]. In addition, Figure S2 shows the HPLC–ESI–TOF–MS chromatogram of apple pomace with seed extracts, showing the location of amygdalin at time 3.47 min.…”
Section: Resultssupporting
confidence: 66%
“…The method has already been successfully implemented for analysis of e.g., nonsteroidal anti-inammatory agents, volatile organic compounds, hormones, avonoids, pesticides, or antioxidants, and is a very suitable technique for the fast and reliable detection of a wide range of analytes, omitting a demanding pre-separation or extraction steps. 26,[31][32][33][34][35][36] The main feature of FAPA ionization mode is connected with an external ionization source, which is a plasma generated from helium owing between two electrodes. Analytes introduced to the plasma are immediately ionized and directed to the spectrometer through the owing gas (Fig.…”
Section: Investigation Of Adsorption Of Various Chalconesmentioning
confidence: 99%
“…Nevertheless, there remains a dearth of research addressing the alterations of chiral components in food. For instance, amygdalin can undergo interconversion between its R ‐ and S ‐configurations under alkaline conditions (Guć et al., 2020). These observations underscore the pressing need for further investigations regarding the effects of chiral compounds in food, particularly in relation to their molecular configurations and potential implications for safety and health.…”
Section: Introductionmentioning
confidence: 99%